The antidepressant-like effects of fluvoxamine in mice involve the mTOR signaling in the hippocampus and prefrontal cortex. (March 2020) - Xu, Dawei; Wang, Chengniu; Zhu, Xinhui; Zhao, Wei; Jiang, Bo; Cui, Shengyu; Sun, Yuyu; Cui, Zhiming
Highlights: Fluvoxamine treatment reversed the effects of CUMS on the hippocampal mTOR signaling. Fluvoxamine treatment restored the effects of CUMS on mTOR in the prefrontal cortex. Blockade of the mTOR system prevented the antidepressant effects of fluvoxamine in mice. Abstract: Recent studies have suggested that activation of the mammalian target of rapamycin (mTOR) signaling may be related to antidepressant actions. Although thought as a selective serotonin reuptake inhibitor (SSRI), the antidepressant mechanisms of fluvoxamine remain elusive. Therefore, this study aims to evaluate whether mTOR underlies the antidepressant-like effects of fluvoxamine. Male C57BL/6 J mice were subjected to 8 weeks of chronic unpredictable mild stress (CUMS) with fluvoxamine administered during the last 2 weeks. Western blotting analyses were then used to assess the expression of the mTOR signaling cascade in the hippocampus and prefrontal cortex (PFC) among all groups. The selective inhibitor of mTOR, rapamycin, was further used. It was found that fluvoxamine treatment fully reversed the effects of CUMS on the mTOR signaling in the hippocampus and PFC, and the usage of rapamycin significantly prevented the antidepressant-like effects of fluvoxamine in the CUMS model of depression. Taken together, the mTOR system is involved in the antidepressant mechanisms of fluvoxamine.